MOUNT DORA DISASTER RECOVERY IMPLEMENTATION. (American City & County, 2013)
The article reports that Mount Dora, Florida uses Quorum, which is a disaster recovery solution. It states that 25 servers of the city are protected by the system. It mentions that the system runs an automatic test daily and after testing it sends an automatic report through email. It highlights that city's infrastructure is secured even if information technology (IT) issues occur.